Early Results of Extreme Hypofractionation Using Stereotactic Body Radiation Therapy for High-risk, Very High-risk and Node-positive Prostate Cancer. Issue 7 (July 2018) - Murthy, V.; Gupta, M.; Mulye, G.; Maulik, S.; Munshi, M.; Krishnatry, R.; Phurailatpam, R.; Mhatre, R.; Prakash, G.; Bakshi, G.
Abstract: Aims: Stereotactic body radiotherapy (SBRT) in low- and intermediate-risk prostate cancer has shown encouraging results. However, its use in high-risk patients is limited due to lack of data regarding adequate radiotherapy dose, need for pelvic nodal treatment and androgen deprivation therapy. Herein we report our experience of SBRT in this subgroup. Materials and methods: Analysis of a prospectively maintained database of 68 consecutive patients of the National Comprehensive Cancer Network (NCCN) high-risk, very high-risk and node-positive adenocarcinoma prostate treated with SBRT was undertaken. All patients were treated with rotational intensity-modulated radiotherapy with daily image guidance. The dose delivered to the prostate and gross node was 35–37.5 Gy in 5 alternate day fractions. Node-positive patients received 25 Gy to pelvic nodal regions until the common iliac nodes. Treatment was delivered in 7–10 days. All patients received long-term androgen deprivation therapy (79% medical and 21% surgical). Results: Most patients (65%) had a Gleason score ≥ 8. The median prostate-specific antigen was 42. Twenty patients were high risk (30%), 11 (16%) very high risk and 37 (54%) node positive. No acute Radiation Therapy Oncology Group grade ≥ 3 genitourinary or gastrointestinal toxicity was noted. Acute grade 2 genitourinary and gastrointestinal toxicity were 12% and 3%, respectively. Late grade 3 genitourinary and gastrointestinal toxicity was 3% and 0%, respectively. There was no increase in acute or late gastrointestinal toxicity with prophylactic pelvic nodal radiotherapy. Prior transurethral resection of prostate ( n  = 11) did not increase toxicity. At a median follow-up of 18 months, 97% patients were alive and 94% were biochemically controlled. Conclusion: SBRT is safe in the treatment of high-risk, very high-risk and node-positive prostate cancer, even with prophylactic pelvic radiotherapy or prior transurethral resection of prostate. Longer follow-up is required to determine efficacy. Highlights: Largest series of SBRT in high-/very high-risk prostate cancer. First in node-positive prostate cancer. Only series reporting toxicity with prior TURP. Comparable early and late toxicity to moderate hypofractionation. SBRT proved to be safe and effective even with prophylactic pelvic treatment and prior TURP.